2023
DOI: 10.31992/0869-3617-2023-32-1-51-70
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling in Higher Education: Determining Factors of Academic Performance

Abstract: For several decades in the field of data mining in education (EDM), predictive learning has remained one of the most popular and internationally discussed research topics. Specifically, data mining is used to predict educational outcomes such as academic performance, retention, success, satisfaction, achievement and dropout rates. In the management practice of higher education institutions, on the basis of an operational forecast, measures are developed and implemented to support those students who fall into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…For example, in reference [17], the task of forecasting overall academic performance is addressed using data on students' socio-economic status and entrance exam results at a Chinese university, with a four-layer Artificial Neural Network (ANN) being used as the forecasting model. In the study [18], three-layer ANNs are also employed solely for predicting completion of an educational program (forecasting the risk of long-term dropout). The Graduate Grade Point Average (GGPA), the average performance score for the first semester of study, and the year of enrollment at the university were identified as the most important predictors of academic performance.…”
Section: Literature Review Of the Data And Machine Learning Algorithm...mentioning
confidence: 99%
“…For example, in reference [17], the task of forecasting overall academic performance is addressed using data on students' socio-economic status and entrance exam results at a Chinese university, with a four-layer Artificial Neural Network (ANN) being used as the forecasting model. In the study [18], three-layer ANNs are also employed solely for predicting completion of an educational program (forecasting the risk of long-term dropout). The Graduate Grade Point Average (GGPA), the average performance score for the first semester of study, and the year of enrollment at the university were identified as the most important predictors of academic performance.…”
Section: Literature Review Of the Data And Machine Learning Algorithm...mentioning
confidence: 99%